2017
DOI: 10.4081/or.2017.7030
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of common pediatric elbow injuries

Abstract: Normal variations in anatomy in the skeletally immature patient may be mistaken for fracture or injury due to the presence of secondary centers of ossification. Variations in imaging exist from patient to patient based on sex, age, and may even vary from one extremity to the other on the same patient. Despite differences in the appearance of the bony anatomy of the elbow there are certain landmarks and relationships, which can help, distinguish normal from abnormal. We review common radiographic parameters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…A concomitant fracture is seen in up to 39% of cases[ 5 , 7 ]. A retrospective study of 494 proximal radius fractures showed that 25% of the concomitant fractures were missed on the initial analysis of radiographs.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…A concomitant fracture is seen in up to 39% of cases[ 5 , 7 ]. A retrospective study of 494 proximal radius fractures showed that 25% of the concomitant fractures were missed on the initial analysis of radiographs.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Less common are ulnar metadiaphyseal fractures, ulnar fractures as part of a Monteggia fracture-dislocation and medial epicondyle fractures. Risk factors for concomitant fractures include joint effusion, young children, and complete or displaced proximal radius fractures[ 5 , 7 ]. In addition to concomitant fractures, other injury patterns can accompany a proximal radius fracture, such as elbow dislocation or acute longitudinal radioulnar disruption (ALRUD or Essex-Lopresti injury).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Data show that fractures of the pediatric elbow represent approximately 12% of systemic fractures [ 4 ]. Accurate diagnosis and effective treatment can reduce children’s pain, shorten the healing time, and prevent malunion and neurovascular complications [ 5 ].…”
Section: Introductionmentioning
confidence: 99%